Doing more with teams : - Piasecki, Bruce (John Wiley & Sons, Inc., 2013)
A new model for productive teamwork that generates wealth From instincts as ancient as our hunter and gatherer stages, men and women have worked in teams. But what have we really learned about these drives and desires in a lasting way? Does all of the selfishness and scandal in business and government today suggest we have spilt the special sauce of teamwork? Doing More With Teams explores what can be done to encourage a new form a competition so that organizations complete the challenges before them to drive growth and get results. From New York Times bestselling author.